Drug-Related Problems and Pharmacist Intervention at a General Hospital in the Jazan Region, Saudi Arabia - Babelghaith SD; Wajid S; Alrabiah Z; Othiq MAM; Alghadeer S; Alhossan A; Al-Arifi M; Attafi IM (Risk Management and Healthcare Policy, 2020)
Salmeen D Babelghaith, 1 Syed Wajid, 1 Ziyad Alrabiah, 1 Mohammed Abdu M Othiq, 2 Sultan Alghadeer, 1 Abdulaziz Alhossan, 1 Mohamed Al-Arifi, 1 Ibraheem M Attafi 3 1Department of Clinical Pharmacy, College of Pharmacy King Saud University, Riyadh, Saudi Arabia; 2Ministry of Health, Sabya General Hospital, General Directorate of Health Affairs, Jazan, Saudi Arabia; 3Poison Control and Medical Forensic Chemistry Center, General Directorate of Health Affairs, Jazan, Saudi ArabiaCorrespondence: Syed WajidDepartment of Clinical Pharmacy, College of Pharmacy King Saud University, Riyadh, Saudi ArabiaEmail wali@ksu.edu.saObjective: This study examined the incidence of drug-related problems (DRPs) in different inpatient departments along with the medical team response to pharmacist’s action in addressing DRPs at Jazan Hospital, Saudi Arabia.Patients and Methods: This retrospective study was conducted among inpatients at Ministry of Health hospital in Jazan, a region in southwestern Saudi Arabia. We collected data for a 2-year period (from 2016 to 2017). For any detected DRP of the ordered medications for dispensing, the inpatient pharmacist is sending report for that particular DRP with recommendation to the medical team which in turn might accept or reject such recommendation. Serious drug–drug interactions, as part of DRP, were assessed by utilizing three different online DDI checkers, including Lexi-Comp, Medscape, and Drugs.com.Results: The most common type of DRP was serious drug–drug interactions (49%). Over the study period, most incidences of DRPs were decreased. Of the DRPs in 2016 and 2017, antibiotics were the most commonly involved (51% and 69.5%) of cases, respectively, followed by proton pump inhibitors (25.3% and 14.1%) and statins (12.9% and 9.4%). Interestingly, of the 241 interventions for DRPs in 2016, 199 (82.5%) were accepted, resulting in a change in drug therapy (p=0.006). In 2017, 90 (70.3%) interventions out of 128 were accepted by the physician and the drug therapy changed (p=0.029).Conclusion: Pharmacist interventions appear to decrease the incidence of DRPs, which emphasize the importance of an optimal pharmaceutical care plan for clinical care settings.Keywords: pharmacist intervention, drug-related problems, inpatient units, Saudi general hospital, Jazan, Saudi Arabia